Cannabis Withdrawal and Sleep: A Systematic Review of Human Studies. Issue 1 (January 2016) - Gates, Peter; Albertella, Lucy; Copeland, Jan
Background: Sleep problems during withdrawal from cannabis use are a common experience. The details regarding how abstinence from cannabis impacts sleep are not well described. This article reviews the literature including a measure of cannabis withdrawal and sleep in humans. Methods: A literature search using a set of cannabinoid and sleep-related terms was conducted across 8 electronic databases. Human studies that involved the administration of cannabinoids and at least 1 quantitative sleep-related measure were included. Review articles, opinion pieces, letters or editorials, case studies (final N < 8), published abstracts, posters, and non-English articles were excluded. Thirty-six publications were included in the review. Results: Sleep was frequently interrupted during cannabis withdrawal, although the specific mechanisms of disruption remain unclear. Conclusions: Methodological issues in the majority of studies to date preclude any definitive conclusion on the specific aspects of sleep that are affected.